2012
DOI: 10.1371/journal.pone.0048366
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive miRNA Expression Analysis in Peripheral Blood Can Diagnose Liver Disease

Abstract: BackgroundmiRNAs circulating in the blood in a cell-free form have been acknowledged for their potential as readily accessible disease markers. Presently, histological examination is the golden standard for diagnosing and grading liver disease, therefore non-invasive options are desirable. Here, we investigated if miRNA expression profile in exosome rich fractionated serum could be useful for determining the disease parameters in patients with chronic hepatitis C (CHC).MethodologyExosome rich fractionated RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 37 publications
0
121
0
1
Order By: Relevance
“…So far, a number of studies have shown the role of miRNAs in the pathogenesis of liver disease including HCC [19]. Moreover, miRNAs detected in circulating blood are usually present within microvesicles such as exosomes [20,21]; the circulating miRNAs could be markers of HCC progression [22]. However, it is difficult to evaluate the serum miRNA profiles from cancer cells for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…So far, a number of studies have shown the role of miRNAs in the pathogenesis of liver disease including HCC [19]. Moreover, miRNAs detected in circulating blood are usually present within microvesicles such as exosomes [20,21]; the circulating miRNAs could be markers of HCC progression [22]. However, it is difficult to evaluate the serum miRNA profiles from cancer cells for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of two miRNAs (miR-483-5p and miR-671-5p) increased significantly and the expression levels of 14 miRNAs (let7a, miR-106b, miR-1274a, miR-130b, miR-140-3p, miR-151-3p, miR-181a, miR-19b, miR-21, miR-24, miR-375, miR-548l, miR-93, and miR-941) were progressively reduced as liver fibrosis increased. 116 As schistosomal egg-induced immunopathology is an unusual type of chronic liver disease distinguishable from many other liver disease types, it is tempting to speculate that a unique set of circulating miRNAs may be defined to potentially serve as sensitive molecular signatures for assessment of the severity of the fibrotic pathology of schistosomiasis. To date, a set of miRNAs of parasite origin have been identified in both S. japonicum 117,118 and S. mansoni 119,120 and miRNA expression profiles at different developmental stages of S. japonicum have been characterized.…”
Section: Cytokinesmentioning
confidence: 99%
“…An interesting study evaluated miRNA expression in exosome-rich fractionated serum in 64 CHC and 12 NASH patients, and was able to differentiate both CHC from NASH and stage F0 from F1-3 with an accuracy of 87% [38]. Further studies to demonstrate diagnostic and prognostic utility of miRNAs as biomarkers in CLD are needed.…”
Section: Genomic and Proteomic Markers Of Fibrosismentioning
confidence: 99%